Ammoniated tannic acid coating and its preparation method and application
Through the coating composed of amino tannin and Fe3+, the problem of low capture efficiency of circulating tumor cells is solved, and efficient and simple cell capture is achieved, suitable for cancer diagnosis and monitoring.
Patent Information
- Application Number
- CN202310566141.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-19
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-05-19
Smart Images

Figure CN116731595B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biofunctional materials, and relates to a biofunctional material for capturing circulating tumor cells, a manufacturing method and uses thereof, and specifically relates to an amino tannic acid coating, a preparation method and uses thereof. Background Art
[0002] Cancer is a serious threat to human health and is the second leading cause of death worldwide. 90% of cancer-related deaths are caused by the metastasis of cancer cells. Circulating tumor cells (CTCs) are a general term for a type of tumor cells that escape from the primary tumor or metastatic site and enter the human peripheral blood circulation system and may form new cancer lesions in important distant organs. They show the same spatial and temporal heterogeneity as the primary tumor and are an important determinant of cancer metastasis and recurrence. Therefore, CTCs are considered to be effective biomarkers for diagnosis, monitoring and prognosis assessment.
[0003] CTCs are rare and heterogeneous, which makes it very difficult to capture CTCs efficiently and broadly in clinical practice. At present, the separation methods of CTCs are mainly based on differences in physical properties and biological affinity, and there are few studies on CTCs separation methods based on chemical modification. The purity of cancer cells captured by separation methods based on physical properties is low, while separation methods based on differences in biological affinity cannot identify CTCs that do not express or lowly express EpCAM. Using a single EpCAM antibody to capture CTCs often results in false negative results.
[0004] Tannic acid (TA) is a water-soluble polyphenolic hydroxyl compound with low price. It can be extracted from plants such as green tea and oak. TA is considered to be an ideal crosslinker due to its rich non-covalent interactions and good chemical reaction properties, and exhibits excellent adhesion on the surfaces of various materials. In addition, TA also has antioxidant, antibacterial and anti-inflammatory properties. TA can act as a "multidentate" ligand, providing strong metal chelating ability through deprotonation, and can bind Fe 3+ Coordination forms a cross-linked network. As in the document Chemistry of Materials, 2018, 30(13): 4372-4382, Liwei Yang et al. constructed a layer-by-layer self-assembled TA-Fe coating by chemical modification, which can capture cancer cells rapidly and broadly without the need for immobilized capture antibodies, and the survival rate of captured cells can reach 90%. However, the preparation steps of the layer-by-layer self-assembled coating are cumbersome, the raw material utilization rate is less than 1%, and the cancer cell capture rate is only 76%. In order to simplify the steps and improve the raw material utilization rate, the coating is prepared by a one-step method based on solvent evaporation of tannic acid particles, but the stability of the prepared coating is very poor. This is because TA and Fe have strong rigidity, which limits the degree of cross-linking between the two.
[0005] Aminated tannic acid is prone to oxidative self-polymerization to form high molecular weight flexible substances, which can increase the rigid Fe 3+ The cross-linking degree is conducive to the rapid and efficient preparation of tannic acid coatings by a one-step method, and the surface of the amino tannic acid coating is positively charged, which is conducive to the adhesion of negatively charged CTCs, and a CTCs capture rate of nearly 90% can be achieved without modifying specific recognition molecules. At present, there is no reported method for using amino tannic acid coatings to capture circulating tumor cells. Summary of the invention
[0006] The present invention is completed based on solving the existing technical problems, and its purpose is to provide an amino tannic acid coating for capturing tumor cells and a preparation method thereof.
[0007] The present invention is achieved through the following technical solutions:
[0008] The first aspect of the present invention:
[0009] An aminated tannic acid coating is composed of aminated tannic acid particles, wherein the aminated tannic acid particles are composed of aminated tannic acid (TAA) and Fe 3+ The TAA is obtained by amino modification of TA molecules. The TA molecules contain abundant phenolic hydroxyl groups that can be modified by chemical functional groups. 3+ It is a good central metal ion and can coordinate with multidentate ligands through metal chelation to form a network structure.
[0010] The TAA is easily oxidatively self-polymerized in deionized water, and the surface is positively charged after oxidative self-polymerization in water.
[0011] The Fe 3+ , the coordination only occupies a small part of the phenolic hydroxyl binding sites, thus retaining the biological activity of the TA molecule.
[0012] The second aspect of the present invention:
[0013] A method for preparing an aminated tannic acid coating comprises the following steps:
[0014] (1) Dissolve TA in an organic solvent and stir the mixture thoroughly to obtain a TA solution.
[0015] (2) Adding an amino-introducing agent containing an amino-protecting group and a base to the above TA solution in sequence, heating and stirring under a protective gas to obtain an amino-protecting group-containing TA solution.
[0016] (3) After the above-mentioned amino-protecting group-containing amino-TA solution is cooled to room temperature, deionized water is added thereto for dilution. Acid is then added to the reaction solution for acidification, and the acidified solution is extracted with an extractant. The separated extraction layers are combined and then washed twice with deionized water to obtain an acid-washed amino-protecting group-containing amino-TA solution.
[0017] (4) Adding a desiccant to the above-mentioned acid-washed amino-containing protective group-aminated TA solution to dry it, thereby obtaining a dry acid-washed amino-containing protective group-aminated TA.
[0018] (5) The dried acid-washed amino-containing protective group-containing TA is filtered, and then the solvent is removed by rotary evaporation, and an organic solvent is added to dissolve the oily substance after rotary evaporation. Acidic gas is then introduced into the organic solvent for continuous bubbling. The reaction mixture is stirred at room temperature, and the solvent is removed by rotary evaporation to obtain impure TAA.
[0019] (6) The impure TAA is dialyzed, the solvent is removed by rotary evaporation, and the TAA is dried to obtain TAA.
[0020] (7) Dissolve the prepared TAA and FeCl3·6H2O in inorganic solvents respectively.
[0021] (8) Place the TAA solution in a centrifuge tube, add FeCl3·6H2O solution, and shake to obtain a TAA / Fe particle suspension.
[0022] (9) Take the TAA / Fe particle suspension and evenly coat it on the substrate surface.
[0023] (10) The solvent on the substrate surface is dried, and then the dried substrate is immersed in deionized water to wash away the non-adherent substances on the surface, and then blown dry with nitrogen to obtain a TAA / Fe coating.
[0024] Furthermore, in step (1), the organic solvent is N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), N,N-dimethylpropionamide (DMP) or N,N-diethylformamide (DEF).
[0025] Furthermore, in step (2), the amino-introducing agent containing an amino protecting group is N-Boc-3-aminopropyl bromide, and the molar ratio of N-Boc-3-aminopropyl bromide to TA is 1 to 5, preferably 1.1; the base is potassium carbonate, potassium hydroxide or sodium hydroxide, preferably potassium carbonate, and the molar ratio of the base to N-Boc-3-aminopropyl bromide is 1.5 to 5, preferably 3; the protective gas is nitrogen or argon, preferably nitrogen; and the heating temperature is 50 to 80°C, preferably 60 to 70°C.
[0026] Furthermore, in step (3), the volume of deionized water added for dilution is 3 to 10 times, preferably 5 to 8 times, the volume of the organic solvent in step (1); the acid is hydrochloric acid, nitric acid or sulfuric acid, preferably hydrochloric acid; the concentration of the acidic solution is 4 to 10 mol / L, preferably 4 to 6 mol / L. The extractant is ethyl acetate.
[0027] Furthermore, in step (4), the desiccant is anhydrous sodium sulfate, anhydrous magnesium sulfate or anhydrous calcium chloride, preferably anhydrous sodium sulfate. The drying time is 4 to 12 hours, preferably 8 to 12 hours.
[0028] Furthermore, in step (5), the organic solvent is ethanol, n-butanol or acetone, preferably ethanol; the acidic gas is hydrogen chloride gas; and the bubbling time is 1 to 4 hours, preferably 2 to 4 hours.
[0029] Furthermore, in step (6), the dialysate is anhydrous ethanol. Drying uses an external heating system or an internal heating system, but there is no specific limitation. For example, the drying is normal pressure drying or reduced pressure drying, preferably vacuum drying. In addition, the drying is performed using a fixed electric furnace, a fluidized electric furnace, a rotary electric furnace, a combustion furnace or a microwave system.
[0030] Furthermore, in step (7), the inorganic solvent is deionized water.
[0031] Furthermore, in step (8), the mass ratio of TAA to FeCl3·6H2O is 0.25 to 1.5, preferably 1.
[0032] Furthermore, in step (9), the volume of the tannic acid particle suspension coated on each square centimeter of the substrate is 20 to 40 μL, preferably 30 μL. The substrate is a glass substrate, and the treatment method is as follows: put the glass sheet into a piranha solution (hydrogen peroxide (30%) and concentrated sulfuric acid (98%) are prepared according to a volume ratio of 3:7, note: piranha solution reacts violently with organic matter and should be handled with caution) and boil for 30 minutes, wash the cooled glass sheet with anhydrous ethanol three times, then rinse with ultrapure water three times, and blow dry with nitrogen to obtain a hydrophilic substrate material.
[0033] Furthermore, in step (10), the drying temperature is 20-40°C, preferably 37°C.
[0034] The third aspect of the present invention:
[0035] Use of an amino tannic acid coating in the field of circulating tumor cell capture.
[0036] Beneficial effects of the present invention: The amino tannic acid coating of the present invention can capture circulating tumor cells quickly and efficiently. The method for capturing circulating tumor cells provided by the present invention does not require modification of specific cancer cell recognition antibodies or nucleic acid aptamers, can achieve the capture of different types of cancer cells, and has the advantages of simple operation, low cost, high sensitivity, and high capture rate. The prepared amino tannic acid coating can be used to capture circulating tumor cells in peripheral blood, and is expected to be applied to early diagnosis, monitoring and prognosis of cancer patients, separation of cancer cells, and blood purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a scanning electron microscope image of the TAA / Fe particles prepared in Example 1, with a scale bar of 2 μm.
[0038] Figure 2 This is a scanning electron microscope image of the TAA / Fe coating prepared in Example 1, with a scale bar of 30 μm. DETAILED DESCRIPTION
[0039] Hereinafter, examples are given to illustrate the specific embodiments of the present invention, but the embodiments of the present invention are not limited by the following examples, and any selection and change can be made within the scope that does not affect the technical effects to be achieved by the present invention. If no specific conditions are specified in the embodiments and test examples, the conventional conditions or the conditions recommended by the manufacturer are followed, and the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.
[0040] Example 1
[0041] This embodiment involves the use of TAA / Fe coating as the coating, and uses human breast cancer cells (MDA-MB-231 cells) purchased from the cell bank of the Chinese Academy of Sciences as the circulating tumor cell model to be captured, and further describes and verifies the capture system of the present invention, including the following steps:
[0042] 1. Preparation of TAA / Fe coating for circulating tumor cell capture
[0043] First, TA (8.00 g, 4.7 mmol) was dissolved in 20 mL of N,N-dimethylformamide, and then N-Boc-3-aminopropyl bromide (1.19 g, 5 mmol) and K2CO3 (2.07 g, 15 mmol) were added in sequence, and the reaction mixture was stirred at 60°C under a nitrogen flow for 6 hours.
[0044] Next, after cooling to room temperature, 200 mL of deionized water was added to the reaction mixture. 4 mol / L hydrochloric acid solution was added to the reaction solution for acidification, and the acidified solution was extracted three times with 90 mL of ethyl acetate. The separated ethyl acetate layers were combined, washed twice with 60 mL of deionized water, and dried overnight with anhydrous sodium sulfate.
[0045] Next, the dried reactant was filtered, and then the solvent was removed by rotary evaporation. 20 ml of anhydrous ethanol was added to dissolve the oily substance after rotary evaporation. Concentrated sulfuric acid was added dropwise to the NaCl solid to generate HCl gas, and the generated gas was continuously bubbled into the solution for 2 hours. The reaction mixture was stirred at room temperature for another 24 hours, and the solvent was removed by rotary evaporation. Dialysis was performed in anhydrous ethanol for 2 days, the solvent was removed by rotary evaporation, and TAA was obtained by vacuum drying for 18 hours.
[0046] Next, 2 mg / mL TAA and FeCl3·6H2O solutions were prepared respectively, 500 μL of TAA solution was taken into a 1.5 mL centrifuge tube, and then 500 μL of FeCl3·6H2O solution was added and shaken for 30 s to obtain a TAA / Fe particle suspension.
[0047] Next, 30 μL of the TAA / Fe particle suspension was evenly coated on the surface of the glass substrate and dried at 37° C. The prepared TAA / Fe coating was soaked in deionized water for 10 min and then dried with nitrogen.
[0048] Figure 1 This is a scanning electron microscope image of TAA / Fe particles. The size of the particles formed is 3-5μm, and the particle surface is positively charged. Figure 2 is a scanning electron microscope image of the TAA / Fe coating. The above results show that the coating surface prepared by the one-step method of solvent evaporation of amino acid tannic acid particles is uniform and continuous. The surface of the prepared TAA / Fe coating is positively charged.
[0049] 2. Prepare circulating tumor cell samples to be tested
[0050] Take 100 μL of MDA-MB-231 cell suspension, count and calculate the cell suspension concentration using a cell counter. Take a certain amount of the above cell suspension and dilute it with DMEM cell culture medium to a cell density of 1*10 5 Pieces / mL.
[0051] 3. Capture experiment
[0052] The glass substrate immobilized with the TAA / Fe coating in step 1 above was placed in a 24-well plate, and then 500 μL of the cell suspension mixed evenly in step 2 above was added into the wells, and then cultured in a 37° C. constant temperature incubator for 90 minutes.
[0053] After cell capture, the captured cells were fixed with 4% paraformaldehyde (PBS) for 30 min, washed three times with PBS, 500 μL of 10 μg / mL DAPI solution was added to each well, the cells were stained for 15 min, washed three times with PBS again, and the samples were placed under an inverted fluorescence microscope to observe the adhered cells. The cells on the surface of the TAA / Fe coating were randomly photographed, and the number of adhered cells was counted using the software Image j.
[0054] The cell capture rate was calculated as follows:
[0055]
[0056] where n is the number of cells captured by a single TAA / Fe coating and N is the number of cells added initially.
[0057] The cancer cell capture rate of each field of view is calculated by the above formula, and then the average value is taken to obtain the capture rate of circulating tumor cells by the TAA / Fe coating.
[0058] After cell capture, the viability of cells captured by TAA / Fe coating was determined by fluorescein diacetate (FDA) and propidium iodide (PI) live and dead staining: FDA dyed captured live cells green, and PI dyed captured dead cells red. 1μg / mL FDA solution (PBS) and 1μg / mL PI solution (PBS) were added to the surface of TAA / Fe coating after cell capture, and the staining was carried out in the dark for 10 minutes. The samples were observed under an inverted fluorescence microscope, and random photos were taken and counted.
[0059] The capture cell viability calculation method is as follows:
[0060]
[0061] Where n is the number of captured live cells and m is the number of captured dead cells.
[0062] The cancer cell capture rate in each field of view is calculated by the above formula, and then the average value is taken to obtain the cell viability of circulating tumor cells captured by the TAA / Fe coating.
[0063] The above experimental results show that the capture rate of MDA-MB-231 cells by TAA / Fe coating reaches 90%, and the proportion of live cells among the captured cells is close to 100%, indicating that the coating can achieve efficient capture of circulating tumor cells.
[0064] Example 2
[0065] The coating used in this embodiment is TAA / Fe coating, and the human breast cancer cell (MDA-MB-231, MCF-7) cell lines, human epidermal cancer cells (A431) and human lung cancer cells (A549) purchased from the cell bank of the Chinese Academy of Sciences are used as circulating tumor cell models to be captured. The capture system of the present invention is further explained and verified, including the following steps:
[0066] 1. Preparation of TAA / Fe coating for circulating tumor cell capture
[0067] The TAA / Fe coating preparation method used in this embodiment is consistent with that in the above-mentioned embodiment 1.
[0068] 2. Prepare circulating tumor cell samples to be tested
[0069] Take 100 μL of MDA-MB-231, MCF-7, A431, and A549 cells respectively, count and calculate the concentration of the cell suspension using a cell counter. Take a certain amount of the above cell suspension and dilute it with DMEM cell culture medium to a cell density of 1*10 5 Pieces / mL.
[0070] 3. Capture experiment
[0071] The glass substrate immobilized with the TAA / Fe coating in step 1 above was placed in a 24-well plate, and then 500 μL of the MDA-MB-231, MCF-7, A431 and A549 cell suspensions mixed evenly in step 2 above were added to the wells, and then cultured in a 37°C constant temperature incubator for 90 minutes.
[0072] After cell capture, the captured cells were fixed with 4% paraformaldehyde (PBS) for 30 min, washed three times with PBS, 500 μL of 10 μg / mL DAPI solution was added to each well, the cells were stained for 15 min, washed three times with PBS again, and the sample was placed under an inverted fluorescence microscope to observe the adhered cells. The cells on the surface of the TAA / Fe coating were randomly photographed, and the number of captured cells was statistically counted using the software Image j. The cancer cell capture rate calculation method was the same as in Example 1.
[0073] The experimental results showed that the capture rates of the prepared TAA / Fe coating for MDA-MB-231, MCF-7, A431 and A549 cells were 88%, 87%, 87% and 86%, respectively, indicating that the coating can achieve efficient capture of different cancer cell lines and has good broad spectrum.
[0074] Example 3
[0075] This embodiment involves the use of TAA / Fe coating as the coating, and uses the human breast cancer cell (MDA-MB-231) cell line purchased from the cell bank of the Chinese Academy of Sciences as the circulating tumor cell model to be captured, and further describes and verifies the capture system of the present invention, including the following steps:
[0076] 1. Preparation of TAA / Fe coating for circulating tumor cell capture
[0077] The TAA / Fe coating preparation method used in this embodiment is consistent with that in the above-mentioned embodiment 1.
[0078] 2. Prepare circulating tumor cell samples to be tested
[0079] Take 100 μL of MDA-MB-231 cell suspension, count and calculate the concentration of the cell suspension using a cell counter. Take a certain amount of the above cell suspension and dilute it with DMEM cell culture medium to a cell density of 200 cells / mL, 400 cells / mL, 800 cells / mL, 1200 cells / mL, 1600 cells / mL, and 2000 cells / mL.
[0080] 3. Capture experiment
[0081] The glass substrate immobilized with the TAA / Fe coating in step 1 above was placed in a 24-well plate, and then 500 μL of the MDA-MB-231 cell suspensions with cell densities of 200 cells / mL, 400 cells / mL, 800 cells / mL, 1200 cells / mL, 1600 cells / mL, and 2000 cells / mL mixed in step 2 above were added to the wells, and then cultured in a 37°C constant temperature incubator for 90 minutes.
[0082] After cell capture, the captured cells were fixed with 4% paraformaldehyde (PBS) for 30 min, washed three times with PBS, 500 μL of 10 μg / mL DAPI solution was added to each well, the cells were stained for 15 min, washed three times with PBS again, and the sample was placed under an inverted fluorescence microscope to observe the adhered cells. The cells on the surface of the TAA / Fe coating were randomly photographed, and the number of captured cells was statistically counted using the software Image j. The cancer cell capture rate calculation method was the same as in Example 1.
[0083] The experimental results show that when the number of MDA-MB-231 cells input is 100, 200, 400, 600, 800, and 1000, respectively, the capture rate of MDA-MB-231 cells by TAA / Fe coating is shown in Table 1 below:
[0084] Table 1
[0085]
[0086]
[0087] As can be seen from Table 1 above, the capture rate under different MDA-MB-231 cell numbers is almost 87%, which indicates that the TAA / Fe coating has high sensitivity and can achieve efficient capture of rare cancer cells.
[0088] Comparative Example 1
[0089] This comparative example involves the use of TA-Fe coating, compares the capture rate of cancer cells captured by TA-Fe coating and TAA / Fe coating, uses human breast cancer cell (MDA-MB-231) cell line purchased from the cell bank of the Chinese Academy of Sciences as the circulating tumor cell model to be captured, and further explains and verifies the capture system of the present invention, including the following steps:
[0090] 1. Preparation of TA-Fe coating
[0091] Prepare 3.2mg / mL TA solution and 0.8mg / mL FeCl3 solution, place the glass slide (1.5cm in diameter) in a 24-well plate, add 1mL TA solution to each well, shake for 20s, and let stand for 10min; then add 1mL FeCl3 solution, shake for 20s to mix the solution evenly, and react for 3min; then aspirate the solution, and then wash three times with deionized water to complete one layer of modification. Starting from the second layer, first add 1mL FeCl3 solution, then add 1mL TA solution, quickly shake for 20s to mix evenly, and react for 3min; then aspirate the solution, and then wash three times with deionized water; repeat the modification for three layers to finally obtain a TA-Fe coating.
[0092] 2. Prepare circulating tumor cell samples to be tested
[0093] The circulating tumor cell samples to be tested in this example are the same as those in Example 1.
[0094] 3. Capture experiment
[0095] The method for capturing MDA-MB-231 cells and the method for calculating the capture rate in this example are consistent with those in Example 1 above.
[0096] The experimental results showed that the capture rate of the prepared TA-Fe coating for MDA-MB-231 cells was 74%, which was significantly lower than the capture rate of the TAA / Fe coating (90%), indicating that the TAA / Fe coating can achieve efficient capture of circulating tumor cells and has good development prospects.
Claims
1. A method for preparing an aminated tannic acid coating, characterized in that: The coating is composed of aminated tannic acid particles, wherein the aminated tannic acid particles are composed of aminated tannic acid TAA and Fe 3+ Composition: The amino tannic acid TAA is obtained by aminated modification of tannic acid molecules; the Fe 3+ It is the central metal ion, which coordinates with the multidentate ligand through metal chelation to form a network structure; The preparation method comprises the following steps: (1) dissolving tannic acid in an organic solvent and stirring the mixture sufficiently to completely dissolve the tannic acid to obtain a tannic acid solution; (2) adding an amino-introducing agent containing an amino-protecting group and a base to the above-mentioned tannic acid solution in sequence, heating and stirring under protective gas to obtain an amination tannic acid solution containing an amino-protecting group; wherein the amino-introducing agent containing an amino-protecting group is N-Boc-3-aminopropyl bromide, and the molar ratio of N-Boc-3-aminopropyl bromide to tannic acid is 1 to 5; the molar ratio of the base to N-Boc-3-aminopropyl bromide is 1.5 to 5; and the heating temperature is 50 to 80°C; (3) After cooling the above-mentioned amino-protecting group-containing amino-tannic acid solution to room temperature, deionized water is added thereto for dilution; then an acid is added to the reaction solution for acidification, wherein the concentration of the acidic solution is 4 to 10 mol / L; the acidified solution is extracted with an extractant; the separated extraction layers are combined and then washed twice with deionized water to obtain an acid-washed amino-tannic acid solution containing an amino-protecting group; (4) adding a desiccant to the above-mentioned acid-washed amino-containing protecting group-aminated tannic acid solution to dry the solution, thereby obtaining dry acid-washed amino-containing protecting group-aminated tannic acid; (5) filtering the dried acid-washed amino tannic acid containing an amino protecting group, and then removing the solvent by rotary evaporation, adding an organic solvent to dissolve the oily substance after rotary evaporation; then continuously bubbling an acidic gas into the organic solvent; stirring the reaction mixture at room temperature, and removing the solvent by rotary evaporation to obtain TAA containing impurities; (6) dialyzing the impure TAA, removing the solvent by rotary evaporation, and drying to obtain TAA; (7) dissolving the prepared TAA and FeCl3·6H2O in an inorganic solvent respectively; (8) Put the TAA solution in a centrifuge tube, add FeCl3·6H2O solution, and shake to obtain a TAA / Fe particle suspension; wherein the mass ratio of TAA to FeCl3·6H2O is 0.25-1.5; (9) Take the TAA / Fe particle suspension and evenly coat it on the substrate surface; (10) Drying the solvent on the substrate surface at a temperature of 20 to 40 °C; then immersing the dried substrate in deionized water to wash away the non-adherent substances on the surface, and blowing it dry with nitrogen to obtain a TAA / Fe coating.
2. The preparation method according to claim 1, characterized in that: In the step (1), the organic solvent is N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropionamide or N,N-diethylformamide; in the step (2), the base is potassium carbonate, potassium hydroxide or sodium hydroxide, and the protective gas is nitrogen or argon.
3. The preparation method according to claim 1 or 2, characterized in that: In the step (3), the volume of deionized water added for dilution is 3 to 10 times the volume of the organic solvent in the step (1); the acid is hydrochloric acid, nitric acid or sulfuric acid; and the extractant is ethyl acetate.
4. The preparation method according to claim 1 or 2, characterized in that: In the step (4), the desiccant is anhydrous sodium sulfate, anhydrous magnesium sulfate or anhydrous calcium chloride, and the drying time is 4 to 12 hours. In the step (5), the organic solvent is ethanol, n-butanol or acetone, the acidic gas is hydrogen chloride gas, and the bubbling time is 1 to 4 hours.
5. The preparation method according to claim 1 or 2, characterized in that: In step (6), the dialysate is anhydrous ethanol; and in step (7), the inorganic solvent is deionized water.
6. The preparation method according to claim 1 or 2, characterized in that: In the step (9), the volume of the TAA / Fe particle suspension coated on each square centimeter of the substrate is 20-40 μL; the substrate is a glass substrate, and the treatment method is as follows: the glass sheet is placed in a piranha solution and boiled for 30 minutes, the cooled glass sheet is washed three times with anhydrous ethanol, and then rinsed three times with ultrapure water, and dried with nitrogen to obtain a hydrophilic substrate material, wherein the piranha solution is prepared by mixing 30% hydrogen peroxide and 98% concentrated sulfuric acid in a ratio of 3:7 by volume.
7. The preparation method according to claim 1, characterized in that: In step (2), the molar ratio of N-Boc-3-aminopropyl bromide to tannic acid is 1.1, the base is potassium carbonate, the molar ratio of the base to N-Boc-3-aminopropyl bromide is 3, the protective gas is nitrogen, and the heating temperature is 60-70°C; in step (3), the volume of deionized water added for dilution is 5-8 times the volume of the organic solvent in step (1), the acid is hydrochloric acid, and the concentration of the acidic solution is 4-6 mol / L; in step (4), the desiccant is anhydrous sodium sulfate, and the drying time is 8-12 h; in step (5), the organic solvent is ethanol, and the bubbling time is 2-4 h; in step (8), the mass ratio of TAA to FeCl3·6H2O is 1; in step (9), the volume of the TAA / Fe particle suspension coated on each square centimeter of the substrate is 30 μL; in step (10), the drying temperature is 37°C.
8. Use of the amino tannic acid coating prepared by the method of claim 1 in the field of capturing circulating tumor cells, which is not a method for diagnosing or treating a disease.
Citation Information
Patent Citations
Preparation method of tannin-histidine metal complex
CN111662342A
Methotrexate-entrapped iron-tannic acid complex, and preparation method and application thereof
CN111821470A